Breach of promise over issue of continuity seen as catalyst - Daily Express, (KK) (Daily Express (KK), 2014)
KUALA LUMPUR: Datuk Seri Ahmad Said's ungentlemanly conduct over the issue of continuity of the Terengganu leadership is seen as the catalyst to the political crisis afflicting the East Coast state.